Enhanced Microscopic Dynamics of a Liver Lipid Membrane in the Presence of an Ionic Liquid - Sharma, Veerendra K.; Ghosh, Sajal K.; García Sakai, Victoria; Mukhopadhyay, R. (Frontiers in Chemistry, 2020)
Ionic liquids (ILs) are an important class of emerging compounds, owing to their widespread industrial applications in high-performance lubricants for food and cellulose processing, despite their toxicity to living organisms. It is believed that this toxicity is related to their actions on cellular membrane. Hence, it is vital to understand the interaction of ILs with cell membranes. Here, we report on the effects of an imidazolium based IL, 1-decyl-3-methylimidazolium tetrafluoroborate (DMIM[BF4]), on the microscopic dynamics of a membrane formed by liver extract lipid, using quasielastic neutron scattering (QENS). The presence of significant quasielastic broadening indicates stochastic molecular motions of the lipids to be active in the system. Two distinct molecular motions (i) lateral motion of the lipid within the membrane leaflet and (ii) localised internal motions of the lipid, are found to contribute to the QENS broadening. While the lateral motion could be described assuming continuous diffusion, the internal motion is explained on the basis of localised translational diffusion. Incorporation of the IL into the liver lipid membrane is found to enhance the membrane dynamics, by accelerating both lateral and internal motions of the lipids. This indicates that IL induces disorder in the membrane and enhances the fluidity of lipids. This could be explained on the basis of its location in the lipid membrane. Results are compared with various other additives and we provide an indication of a possible correlation between the effects of guest molecules on the dynamics of the membrane and its location within the membrane.